Direction-Controlled Chemical Doping for Reversible G-Phonon Mixing in ABC Trilayer Graphene - Park, Kwanghee (Sci Rep, 2015)
Not only the apparent atomic arrangement but the charge distribution also defines the crystalline symmetry that dictates the electronic and vibrational structures. In this work, we report reversible and direction-controlled chemical doping that modifies the inversion symmetry of AB-bilayer and ABC-trilayer graphene. For the “top-down” and “bottom-up” hole injection into graphene sheets, we employed molecular adsorption of electronegative I(2) and annealing-induced interfacial hole doping, respectively. The chemical breakdown of the inversion symmetry led to the mixing of the G phonons, Raman active E(g) and Raman-inactive E(u) modes, which was manifested as the two split G peaks, G(−) and G(+). The broken inversion symmetry could be recovered by removing the hole dopants by simple rinsing or interfacial molecular replacement. Alternatively, the symmetry could be regained by double-side charge injection, which eliminated G(−) and formed an additional peak, G(o), originating from the barely doped interior layer. Chemical modification of crystalline symmetry as demonstrated in the current study can be applied to other low dimensional crystals in tuning their various material properties.